Assessment of high-tech export dynamics and the impact of its cyclicality on GDP and the country’s production reserves - Makarenko, Petro; Belov, Oleksandr; Makarenko, Andrii; Svystun, Lyudmyla (Technology audit and production reserves, 2025)
The object of this research is the dynamics of high-tech exports and their impact on GDP and production reserves. The instability of high-tech exports can hinder long-term economic growth, particularly in economies where technological sectors play a crucial role in national competitiveness. To address these issues, the research employs an econometric approach that integrates both linear and cyclical components to analyze the structural dynamics of high-tech exports. As a result, the research identifies two dominant economic cycles, lasting 3.8 and 5.7 years respectively, which significantly influence overall export trends. This is attributed to the nature of high-tech industries, where product innovation cycles, shifts in global demand, and technological progress contribute to periodic fluctuations in export volumes. The proposed econometric model offers a more accurate assessment of production reserves by identifying periods of economic acceleration and deceleration. This is achieved through the model’s ability to isolate cyclical components, enabling strategic adjustments in industrial planning, investment policy, and innovation-driven growth. For instance, based on the identified cycles, companies can better align product launch schedules, reconfigure production capacity during demand slowdowns, and optimize export contract volumes during peak growth periods. Compared to conventional forecasting methods, this approach provides a more comprehensive understanding of high-tech export dynamics, enhancing economic stability and industrial resilience. The research also holds practical significance. Specifically, the implementation of adaptive budgetary and industrial strategies that are attuned to cyclical dynamics can reduce the risks of overproduction, shortages, or price volatility. In post-war Ukraine, the findings may facilitate the development of strategic policies aimed at the recovery and modernization of the industrial sector. Given limited resources and the urgent need for innovative reconstruction strategies, the proposed model could serve as a foundation for crisis-responsive planning and the rationalization of investments in priority industries.